Transforaminal versus posterior lumbar interbody fusion for symptomatic single-level spondylolisthesis (LIFT): a multicentre controlled, patient blinded, randomised non-inferiority trialResearch in context - Inge J.M.H. Caelers; Ruud Droeghaag; Suzanne L. de Kunder; Jasper Most; Kim Rijkers; Ronald H.M.A. Bartels; Jos M.A. Kuijlen; Mark H.H.M. Hulsbosch; Wouter L.W. van Hemert; Rob A. de Bie; Henk van Santbrink (Elsevier, 2024)
Summary: Background: The effectiveness of transforaminal lumbar interbody fusion (TLIF) compared to posterior lumbar interbody fusion (PLIF) in patients with single-level spondylolisthesis has not been substantiated. To address the evidence gap, a well-powered randomized controlled non-inferiority trial comparing the effectiveness of TLIF with PLIF, entitled the Lumbar Interbody Fusion Trial (LIFT), was conducted. Methods: In a multicenter randomized controlled non-inferiority trial among five Dutch hospitals, 161 patients were randomly allocated to either TLIF or PLIF (1:1), stratified according to study site. Patients and statisticians were blinded for group assignment. All patients were over 18 years old with symptomatic single-level degenerative, isthmic or iatrogenic lumbar spondylolisthesis, and eligible for lumbar interbody fusion surgery through a posterior approach. The primary outcome was change in disability measured with the Oswestry Disability Index (ODI) from preoperative to one year postoperative. The non-inferiority limit was set to 7.0 points based on the MCID of ODI. Secondary outcomes were change in quality-adjusted life years (QALY) assessed with EuroQol 5 Dimensions, 5 Levels (EQ-5D-5L) and Short Form Health Survey (SF-36), as well as back and leg pain (Numerical rating scale, NRS), anxiety and depression (Hospital Anxiety Depression Scale; HADS), perioperative blood loss, duration of surgery, duration of hospitalization, and complications. Trial registration: Netherlands Trial Registry, number 5722 (registration date March 30, 2016), Lumbar Interbody Fusion Trial (LIFT): A randomized controlled multicenter trial for surgical treatment of lumbar spondylolisthesis. Findings: Patients were included between August 2017 and November 2020. The total study population was 161 patients. Total loss-to-follow-up after one year was 16 patients. Per-protocol analysis included 66 patients in each group. In the TLIF group (mean age 61.6, 36 females), ODI improved from 46.7 to 20.7, whereas in the PLIF group (mean age 61.9, 41 females), it improved from 46.0 to 24.9. This difference (−4.9, 90% CI −12.2 to +2.4) did not reach the non-inferiority limit of 7.0 points in ODI. A significant difference in the secondary outcome measurement, QALY (SF-36), was observed in favor of TLIF (P < 0.05). However, this was not clinically relevant. No difference was found for all other secondary outcome measurements; PROMs (EQ-5D, NRS leg/back, HADS), perioperative blood loss, duration of surgery, duration of hospitalization, and perioperative and postoperative complications. Interpretation: For patients with single-level spondylolisthesis, TLIF is non-inferior to PLIF in terms of clinical effectiveness. Disability (measured with ODI) did not differ over time between groups. Funding: No funding was received for this trial.